Faktor yang Berhubungan dengan Pemeriksaan Payudara Sendiri (SADARI) pada Remaja Putri di Dusun II Desa Bawoza’ua Kecamatan Teluk Dalam Kabupaten Nias Selatan : Penelitian - Siregar, Afrahul Padilah; Duha, Ester Lola Kartika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Public awareness of early breast cancer detection remains low. A record 53.7% of the population has never performed breast self-examination (BSE). BSE is one method for early breast cancer detection. While standing upright facing a mirror, systematically palpate and observe the breasts. BSE is performed routinely every month, on the 7th-10th day after menstruation. Objective: The purpose of this study was to determine the relationship between knowledge, attitudes, and sources of information and breast self-examination among adolescent girls in Hamlet II, Bawoza'ua Village. Method: This study used an analytical survey design with a cross-sectional approach, using chi-square data analysis at a 95% confidence level. Primary data collection involved distributing questionnaires directly to adolescents, a sample of 30 respondents. Result : The results of the study showed a relationship between knowledge and breast self-examination (p-value = 0.005 < (α 0.05), attitude and breast self-examination (p-value = 0.000 < (α 0.05), and information sources and breast self-examination (p-value = 0.000 < (α 0.05).Conclusion : The study concluded that there was a relationship between knowledge, attitudes, and information sources and breast self-examination in Bawozau'ua Village, Nias, in 2025.